The Effect of Maternal Anemia on Low Birth Weight: Meta Analysis - Elsa Tursina; Fahmi Adhimukti (Journal of Epidemiology and Public Health, 2022)
Background: Low birth weight is still a global public health problem that is associated with a number of risks. One of the factors that influence the occurrence of LBW is anemia. This study was aimed to estimate the risk of anemia in pregnant women to the incidence of LBW in several countries.Subjects and Method: This study is a meta-analysis with PICO, Population: pregnant women. Intervention: maternal anemia. Comparison: no maternal anemia. Result: LBW. The articles used in this study were obtained from three databases namely Google Scholar, Pubmed, and Science Direct with a cohort study design from 2015 to 2022 that reported Adjusted Odds Odds Ratio in its multivariate analysis. The selection of articles was carried out using the PRISMA flow chart. Analysis of articles using the Review Manager 5.3 application.Results: A total of 9 cohort studies involving 75,807 pregnant women from Taiwan, China, Japan, India, Bangladesh, Iran, and Colombia were selected for systematic review and meta-analysis. The data collected showed that pregnant women who were anemic during pregnancy had a 1.3 times higher risk of giving birth to babies with low birth weight than non-anemic mothers, but this result was not statistically significant (aOR= 1.30; 95% CI= 0.89 to 1.88; p= 0.170). With an intuitive index of 84%, so the effect between the studies is heterogeneous.Conclusion: Mothers who experience anemia during pregnancy have a risk of giving birth to babies with low birth weight. Keywords: anemia, pregnancy, low birth weight Correspondence:Fahmi Adhimukti. Study Program of Midwifery, Diploma IV, Health Polytechnics, Ministry of Health Surakarta. Jl. Tata Bumi 3, Sleman, Yogyakarta, Indonesia. Email: fahmiadhimukti13@gmail.com. Mobile: 085743155133.